Maintaining faith from within: How Chinese Muslim organisations in Indonesia improve converts" understanding of Islam - Abidin, Yusuf Z. (HTS teologiese studies, 2022)
This study discusses the numerous challenges that Chinese Muslims experience as a minority in Indonesia, as well as the role of Chinese Muslim groups in providing them with religious direction. This study employs a phenomenological approach that relies on in-depth interviews with 14 informants who were chosen purposively. According to the study, the obstacles faced are domestic constraints, where they are alienated by their extended family, and social constraints, particularly for those from disadvantaged groups. As a result of this situation, they became acquainted with several Chinese Muslim organisations. Although this phenomena demonstrates a constructive cooperation among Chinese Muslims, it also implies that assimilation efforts with local Muslims are not properly manifested.Contribution: Although the decision to convert to Islam has resulted in exclusion from their extended family, they are still able to maintain their new faith by relying on Islamic organisations run by fellow Chinese Muslims. At the same time, this phenomenon illustrates that their assimilation efforts with local Muslims have not been properly realised.